![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1.A=2^2+2^4+...+2^2010
=> 2^2 A= 2^4+2^6+..+2^2012
=> 2^2 A - A=( 2^4+2^6+..+2^2012 ) -(2^2+2^4+...+2^2010 )
=> 3A= 2^2012 -2^2
=> A= (2^2012-2^2)/3
B=3-3^2+3^3-...-3^2010
=>3B= 3^2 -3^3+3^4-...-3^2011
=> 3B + B = (3^2 -3^3+3^4-...-3^2011) +(3-3^2+3^3-...-3^2010)
=> 4B =3-3^2011
=> B= (3-3^2011)/4
2.
A=3+3^2+..+3^100
=> 3A =3^2+3^3+...+3^101
=> 3A- A = (3^2+3^3+...+3^101)-(3+3^2+..+3^100)
=> 2A=3^101 -3
=> 2A+3 =3^101 mà 2A+3 =3^n
=> n=101
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
bài 8
c) chứng minh \(\overline{aaa}⋮37\)
ta có: \(aaa=a\cdot111\)
\(=a\cdot37\cdot3⋮37\)
\(\Rightarrow aaa⋮37\)
k mk nha
k mk nha.
#mon
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 2:
a) A = 20 + 21 + 22 + 23 + ... + 22010
=> 2A = 2 + 22 + 23 + ... + 22011
=> 2A - A = ( 2 + 22 + 23 + ... + 22011 ) - ( 20 + 21 + 22 + ... + 22010 )
=> A = 22011 - 20
=> A = 22011 - 1
Vì 22011 - 1 > 22010 - 1 nên A > B
A = 2 + 22 + 23 + ... + 22010
=> 2A = 22 + 23 + 24 + ... + 22011
Lấy 2A - A = (22 + 23 + 24 + ... + 22011) - (2 + 22 + 23 + .... + 22010)
A = 22 + 23 + 24 + ... + 22011 - 2 - 22 - 23 - .... - 22010
= 22011 - 2
=> A = 22011 - 2